Correlates of Warning: Territory, Democracy, and Casualty Aversion in Terrorist Tactics. (2020) - Brown, Joseph M.
Abstract: Terrorists attack civilian targets but there is variation in how many civilians they kill. Terrorists may deliberately harm civilians, or they may adopt a less bloody approach, demolishing businesses, transit systems, and other civilian property while employing tactics to avert civilian casualties. One such tactic is to warn civilians before an attack, allowing them to flee the area. With warnings as an example, this study considers why terrorists might adopt casualty-aversion tactics. An analysis of 12, 235 bombings by 131 terrorist groups in the years 1970 to 2016 finds that warnings are most common when terrorists fight democracies and when they lack territorial strongholds. Ideological factors such as religion are not significant predictors of warnings. These findings suggest a need to revisit the claim that religion incentivizes indiscriminate terrorism. They also suggest a strategic logic behind casualty-aversion tactics. Terrorists fighting democracies may spare civilians to appear legitimate in citizens' eyes. Terrorists without strongholds may spare civilians because they rely on the state's population for support. At first glance, my findings appear to contradict civil war literature arguing that militants with strongholds use violence more discriminately. However, terrorism occurs in areas of state control. Militants with strongholds can use indiscriminate terrorism against state-governed civilians without alienating their own supporters elsewhere.